The New York Yankees and the conservative use of space - Bates, Benjamin (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2002)
Abstract New York City’s “Canyon of Heroes”, the stretch of Broadway between Wall Street and City Hall, is often used as a space for celebrating sports, military, or political achievements through a parade. This essay offers an analysis of one iteration of a parade — the New York Yankees 1998 victory parade — and its (re)presentation by NBC. Drawing on Michel de Certeau’s concept of la perruque, the essay argues that a negotiation of multiple readings of this space (macro, micro, and in-between views) allow us to understand how several threads of symbols are woven together to create a politically and economically conservative fabric of spatial representation. The essay offers implications of the conservative use of space for the theorization of spatial theory and critical intervention.